1997
DOI: 10.1148/radiology.202.2.9015051
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of soft-tissue changes after percutaneous transluminal angioplasty and stent placement.

Abstract: The polyester-covered nitinol stent can induce systemic and severe local reactions. These reactions seem to be specific to this type of stent. No definite cause has been established, although the phenomenon appears to be self-limiting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…6,[24][25][26] This postimplantation syndrome is most likely attributable to a foreign body reaction to the implant. Sapoval et al 27 dem-onstrated an edematous response adjacent to the endoprostheses using spiral CT, whereas Kellner et al 28 used magnetic resonance imaging and found perivascular inflammatory reactions in 79% of Dacron-covered endoprostheses they studied.…”
Section: Discussionmentioning
confidence: 99%
“…6,[24][25][26] This postimplantation syndrome is most likely attributable to a foreign body reaction to the implant. Sapoval et al 27 dem-onstrated an edematous response adjacent to the endoprostheses using spiral CT, whereas Kellner et al 28 used magnetic resonance imaging and found perivascular inflammatory reactions in 79% of Dacron-covered endoprostheses they studied.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Sapoval et al (17) reported transient perivascular thickening evident at CT after placement of a stent-graft in the iliac artery. The polyester graft material, not the stainless steel stent, is considered responsible for the inflammatory reaction (19)(20)(21)(22)(23)(24)(25). In both sheep and swine models, histologic examination shows an infiltration of inflammatory cells adjacent to the polyester 1-4 weeks after stent-graft insertion (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Perivascular soft-tissue changes are also reported at magnetic resonance imaging after insertion of a polyestercovered stent in the femoral, iliac, or subclavian arteries (18,19). It may be a foreign-body reaction to polyester (25), or it may be due to the accumulation of proinflammatory substances as part of its processing (19). The authors speculate that such inflammatory reactions are responsible for the Note.-A change in aneurysm diameter between two successive CT scans of ϩ3 mm or more is considered an increase, ϩ3 to Ϫ3 mm as no change, and Ϫ3 mm or more as a decrease.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that some patients develop a “post implantation syndrome” characterized by fever, cutaneous swelling, erythema, leukocytosis, elevated C reactive protein, and perigraft edema (on imaging) following deployment in a native vessel. The reaction is transient and is believed to be a foreign body reaction to Dacron ® (21–24).…”
Section: Definitions and Terminologymentioning
confidence: 99%